Pengembangan Buku Ajar Tematik dengan Lembar Pantauan Orang Tua untuk Kelas 3 Sekolah Dasar - Riduwan, Mochamad; Sulaiman, Sulaiman (SCAD Independent, 2025)
The development of teaching books is carried out to facilitate the needs of students and adapted to the environment of student learning conditions. In this development research presented the efforts of researchers in developing the teaching book tema 2 for grade 3 students at SD Al Hikmah Surabaya. The objectives of this teaching book development research include: (1) describing the development of theme 2 teaching books for grade 3 students that are adapted to the environmental conditions; (2) describe the response and activities of students in using the results of the development of tema 2 teaching books for grade 3. The research method used in the development of this teaching material is Research and Development (R&D). According to Dick & Carrey there are 9 procedures in the development of teaching materials. The results of this development study showed that the development of theme 2 teaching books for grade with parents monitoring sheets is worth developing, as well as responses and activities when using the results of teaching book products shows that students are greatly helped in learning tema 2 Grade 3.